Detection of 9-bp deletion in mitochondrial genome in Vietnamese patients with suspected mitochondrial encephalomyopathy - Hue, Truong Thi; Hue, Pham Minh; Yen, Le Ngoc; Van Anh, Pham Thi; Ngoc, Ngo Diem; Nghia, Phan Tuan (Academia Journal of Biology, 2012)
Mutations in the mitochondrial genome are the cause of many diffenrent diseases, especially encephalomyophathies in humans. However, it is difficult to diagnose the diseases with clinal examinations. DNA analysis is the most reliable method for detection of the mutations. In this study, 72 patients under 20 years old with encephalomyopathies were checked for the presence of the A8344G mutation of MERRF syndrome, the A3243G mutation of MELAS syndrome and a 9-bp deletion between the COII and tRNALysgenes in their mitochondrial genome by using PCR-RFLP and DNA sequencing methods. DNA from peripheral blood samples was used as templates for PCR amplification of mitochondrial DNA (212 bp) fragment starting from 8155 to 8366 position of the human mitochondrial genome. By the polyacrylamide gel electrophoresis, 23 samples were shown to have a bit faster running amplified DNA band than the others. The PCR products were then digested with BanII restriction enzyme, the BanII-digested PCR products again confirmed the difference between the samples. The PCR products of the 23 suspected samples and those from their parents were cloned into pGEM vector, recombinant plasmids were isolated and used for nucleotide sequencing analysis. The obtained nucleotides of the 23 suspected samples were shown to have a 9 bp deletion (CCCCCTCTA) compared with the published reference sequence (J01415.2) and this deletion was inherited from the mother to her child(ren), and appeared in homoplasmy in all the cases. It was also found from this study that none of the 72 subjects carried the A8344G mutation of MERRF syndrome, but only one male patient carried both the 9 bp deletion and A3243G mutation of MELAS syndrome, indicating that there is no reliable relation between the 9 bp (CCCCCTCTA) deletion and A8344G or A3243G mutations.